Identifikasi Pemeliharaan Jaringan Irigasi Di Wilayah Pengamatan Sleman Timur DIY Menggunakan Visualisasi Informasi Data Spasial - Edy Sriyono; Sardi; Sutardi (LPPM Universitas Putera Batam, 2025)
Sleman Regency is one of the regions with extensive agricultural land and the largest rice producer in the Special Region of Yogyakarta Province. To increase rice production in East Sleman, water services are prioritized. This is achieved through the construction of irrigation networks, including dams, canals, culverts, gutters, and sluice gates. This ensures that the operation and maintenance of existing irrigation channels are prioritized. Operations and Maintenance (O&M) are conducted to monitor the condition of irrigation structures in each irrigation area by calculating the extent of physical damage and maintenance costs. To support smooth operation and maintenance activities, a method is needed that can quickly access information on the condition of irrigation structures in each irrigation area using a Spatial Data System, which provides links via HTML Popup, containing information on the condition of the irrigation structures. Through monitoring, damage and maintenance costs are calculated, including damage to the physical structures, such as river stone masonry and plaster. The total volume of river stone masonry in the East Sleman Irrigation Area is 1,188.20 m3 and plastering 3,599.46 m2, while the costs required for the Operation and Maintenance of River Stone Masonry are @ Rp. 929,298.70/m3 so that it requires a cost of Rp. 1,104,201,265.00 and for plastering @ Rp. 52,116.69/m2 so that it requires a cost of Rp. 187,591,905.00. For data on the operation and maintenance needs of each irrigation area, it is easier to store, manage, and display using spatial data from GIS (Geographic Information System) applications.